Challenges and satisfaction in Cardiothoracic Surgery Residency Programmes: insights from a Europe-wide survey. (24th November 2020) - Cerqueira, Rui J; Heuts, Samuel; Gollmann-Tepeköylü, Can; Syrjälä, Simo O; Keijzers, Marlies; Zientara, Alicja; Jarral, Omar A; Jacob, Kirolos A; Haunschild, Josephina; Ariyaratnam, Priyadharshanan; Durko, Andras P; Muller, Patrick; et al.
Abstract: OBJECTIVES: The increasing complexity of surgical patients and working time constraints represent challenges for training. In this study, the European Association for Cardio-Thoracic Surgery Residents' Committee aimed to evaluate satisfaction with current training programmes across Europe. METHODS: We conducted an online survey between October 2018 and April 2019, completed by a total of 219 participants from 24 countries. RESULTS: The average respondent was in the fourth or fifth year of training, mostly on a cardiac surgery pathway. Most trainees follow a 5–6-year programme, with a compulsory final certification exam, but no regular skills evaluation. Only a minority are expected to take the examination by the European Board of Cardiothoracic Surgery. Participants work on average 61.0 ± 13.1 h per week, including 27.1 ± 20.2 on-call. In total, only 19.7% confirmed the implementation of the European Working Time Directive, with 42.0% being unaware that European regulations existed. Having designated time for research was reported by 13.0%, despite 47.0% having a postgraduate degree. On average, respondents rated their satisfaction 7.9 out of 10, although 56.2% of participants were not satisfied with their training opportunities. We found an association between trainee satisfaction and regular skills evaluation, first operator experience and protected research time. CONCLUSIONS: On average, residents are satisfied with their training, despite significant disparities in the quality and structure of cardiothoracic surgery training across Europe. Areas for potential improvement include increasing structured feedback, research time integration and better working hours compliance. The development of European guidelines on training standards may support this. Abstract : Over the past half century, cardiothoracic surgery has evolved from being a sub-speciality within the general surgery department to a distinct medical discipline [1].